Has the distribution of smoking across young adult transition milestones changed over the past 20 years? Evidence from the 1970 British Cohort Study (1996) and Next Steps (2015–16). (December 2021) - Gagné, T.; Schoon, I.; Sacker, A.
Abstract: Introduction: Transitions into work and family life during young adulthood exacerbate differences in the progression of smoking over the life-course. Few have considered how changes in smoking and the transition to adulthood in the past two decades have influenced these relationships over time. Methods: We compared the distribution of smoking at ages 25–26 across transition milestones among 3764 men and 4568 women in the 1970 British Cohort study (1996) and 3426 men and 4281 women in the Next Steps study (2015–16). We regressed occasional and daily smoking status on educational attainment, economic activity, living arrangements, relationship status, and parenthood, adjusting for family background, socio-demographics, and smoking history. Results: There were few differences in associations between the 1996 and 2015-16 samples. Young men and women were less likely to smoke if they had higher education, were homeowners, and cohabited with a partner. Women were less likely to smoke occasionally if they were full-time students, and men were less likely to smoke daily if they were employed full-time and not living with children. However, comparing associations in 2015–16 to 1996: 1) in men, higher education had a weaker negative association and living with a partner had a stronger negative association with daily smoking; 2) in women, independently renting had a weaker positive association with daily smoking. Conclusions: Despite considerable changes in smoking and the transition to adulthood over the past two decades, the distribution of smoking at ages 25–26 across transition milestones has been relatively stable during this time period in Great Britain. Highlights: Smoking at ages 25–26 was associated with economic activity, living arrangements, relationship status, and parenthood in 1996 and 2015–16. Differences in smoking across transition milestones differed by gender. Differences in smoking did not substantially change between 1996 and 2015–16.